Consensus minimum hemoglobin level above which patients with myelodysplastic syndromes can safely forgo transfusions. Issue 12 (14th October 2020) - Tanasijevic, Anna M.; Revette, Anna; Klepin, Heidi D.; Zeidan, Amer; Townsley, Danielle; DiNardo, Courtney D.; Sebert, Marie; DeZern, Amy E.; Stone, Richard M.; Magnavita, Emily S.; Chen, Richard; Sekeres, Mikkael A.; et al.
Abstract: The anemia of MDS often results in decreased quality of life, which is invoked to justify red cell transfusions; however, there are sparse data regarding the minimum hemoglobin (Hb) at which it is safe to forgo transfusions for patients with no evidence of end-organ damage. This issue is even more important in the COVID-19 era, where decreases in blood donations have stressed the blood supply. In March 2018, using a modified Delphi method, we convened a panel of 13 expert MDS clinicians for three iterative rounds to discuss a minimum safe Hb for this population. While the panel was unable to reach the pre-set consensus of 75% for a specific Hb threshold, there was 100% consensus that it be no greater than 7.5 g/dL. Our data suggest that, given no end-organ effects of anemia, patients with MDS can safely forgo transfusions with a Hb of 7.5 g/dL or higher.